Fei Changfang's treatment of Sengyou's anonymous texts - Radich, Michael (JAOS, 2021)
The catalogue entitled Lidai sanbao ji T2034, completed in 598, exerted a profound influence on the shape of the Chinese Buddhist canon. It also features a large number of new ascriptions for canonical texts. Subsequent tradition and modern scholarship have repeatedly found these ascriptions profoundly problematic. Scholarly opinion has been divided about whether the author, Fei Changfang, faithfully reported these suspect ascriptions from other sources (subsequently lost), or was himself their originator. This study analyzes three highly suspect patterns in the treatment of new ascriptions in the Lidai sanbao ji: 1) New ascriptions to the same supposed translator are arbitrarily assigned in batches to titles appearing in delimited, contiguous portions of much longer lists of anonymous texts in the earlier Chu sanzang ji ji. 2) Contradictory information is repeatedly given about the same titles in different parts of the work. 3) Information about titles affected by these two problems is ascribed to an implausibly wide range of earlier catalogues. These three patterns affect numerous separate portions of the Lidai sanbao ji. The Lidai sanbao ji, and not its putative earlier sources, is therefore the common denominator―the bottleneck where these problems collect. The most economical and plausible interpretation is that Fei himself was falsifying his information, whether deliberately or by a rather extreme scholarly negligence. These findings make it all the more imperative to critically evaluate all ascriptions appearing for the first time in the Lidai sanbao ji, including a large number of ascriptions still followed in the canon as it is used today.
Gesehen am 03.12.2025